El impacto de la inteligencia artificial en el derecho penal: Desafíos y oportunidades - Fiallos Martillo, Stefania del Rosario (2025)
This research is framed within the study, specifically in the context of criminal law and the inclusion of artificial intelligence. In this case, the purpose of the research was to analyze the impact of artificial intelligence on criminal law: challenges and opportunities. Therefore, the methodology employed consisted of an exploratory and descriptive study, using a semi-structured interview as a research instrument. Likewise, the main theoretical basis was the study of the impact of artificial intelligence on criminal law, challenges, and opportunities. Among the results obtained, a similar position is observed among the experts consulted and the reviewed bibliography, which highlights the importance of the use of technology based on artificial intelligence in criminal law. Thus, it is concluded that its application should be based on respect for ethical standards and traditional legal knowledge. Thus, the main recommendation is the allocation of resources in this area, as well as the consideration of ongoing training and partnerships with the institutions involved.